EFFECT OF CATALYST PROPERTIES ON THE DEOXYGENATION REACTION OF VEGETABLE OIL AND MODEL COMPOUND TO PRODUCE DIESEL RANGE HYDROCARBON FUELS: A REVIEW - Reva Edra Nugraha; A. R. Yelvia Sunarti; Hellna Tehubijuluw; Zuhriah Mumtazah (Jurnal Kimia Riset, 2022)
The concern associated with the depletion of fossil fuel energy has opened up windows of opportunity for researchers to develop potential energy from renewable resources. The renewable green diesel with diesel range hydrocarbon structure has gained increasing popularity by removing oxygen molecule via direct or hydrodeoxygenation (HDO) and indirect or deoxygenation (DO) reaction.  The catalyst design is an important key to achieve the high quality of diesel range hydrocarbon fuels. The different catalyst properties effect to the distribution of deoxygenated liquid product, the catalytic activity and coke formation during the reaction process. The interaction between metal and support catalyst causes electron transfer to give the synestistic effect. The acidity and basicity play important role in C-C and C-O breaking bond in triglyceride and prevent the coke formation. The pore structure and pore size catalyst provide the accessibility of active sites alleviates the diffusion limitation of reactants/ products.